Green brain - Abdul Shukor, Shureen Faris; Noor Kamal, Nur Amira; Abu Bakar, Shamsul; Baharuddin, Mohd Nasir; Khamis, Shamsul (Universiti Putra Malaysia Press, 2016)
Motivated by large-scale public health problems such as depression and mental health, scientists are looking with renewed interest at how nature affects our brains and bodies. It has been hypothesized that being in nature allows the prefrontal cortex, the brain’s command center, to dial down and rest like an overused muscle. Recovery in the green environment has been proposed as particularly effective due to the calming inherent qualities of nature.